1998
DOI: 10.1099/00221287-144-9-2579
|View full text |Cite
|
Sign up to set email alerts
|

F- phenocopies: characterization of expression of the F transfer region in stationary phase

Abstract: The phenomenon of 'F' phenocopies' in which F+ cells become transferdeficient in stationary phase seems contradictory to the proposed role for F transfer in adaptive mutation during stationary phase induced by nutrient limitation. The expression of a range of transfer genes a t the transcriptional and translational level in stationary phase has been characterized as well as the degree of nicking at the origin of transfer, oriT. Transfer efficiency rapidly decreased in mid-exponential phase, coincident with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 46 publications
3
51
0
Order By: Relevance
“…Because IncF conjugation is strongly inhibited during stationary phase (Frost and Manchak, 1998), the disparity in plasmid persistence probably did not arise from plasmid transfer events. We posit instead that R1-bearing cells had an advantage in survival or proliferation over R1-16-bearing cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because IncF conjugation is strongly inhibited during stationary phase (Frost and Manchak, 1998), the disparity in plasmid persistence probably did not arise from plasmid transfer events. We posit instead that R1-bearing cells had an advantage in survival or proliferation over R1-16-bearing cells.…”
Section: Resultsmentioning
confidence: 99%
“…Transfer of diverse conjugative plasmids is inhibited by stationary phase and high-cell densities (Sudarshana and Knudsen, 1995;Frost and Manchak, 1998). To incorporate this dynamic into our simulations, we included a switch that reduced conjugation rates 1000-fold when C fell below 1/10th of the K m value (see Table 1 for variable definitions).…”
Section: Methodsmentioning
confidence: 99%
“…When FC40 is incubating on lactose, the cells are not proliferating but replication is occasionally initiated at one of the episome's vegetative origins. Nicking at the conjugal origin is persistent in starving cells [61]; when the moving replication fork encounters this nick, the fork will have a high probability of collapsing, creating a double-strand end. Double-strand break repair is then initiated by RecBCD.…”
Section: Model For Adaptive Lac + Mutationmentioning
confidence: 99%
“…This might be explained by the fact that the F-pili mating pairs are formed mainly outside the mature biofilms owing to higher reproductive activity (May et al, 2010), and thus the f1 phage could infect cells located in the outermost of the biofilm. Based on the level of traA transcripts as a measure of transcription of the entire conjugative-factor including the F-pili subunit synthesis (Frost and Manchak, 1998), we found that F-pili transcripts was at the maximum during the microcolony formation stage (6-12 h) and decreased during the late biofilm development and maturation stages (24-48 h) (Figure 2c). Similarly, the number of F-pili declined in the biofilm maturation stage (Figure 2c).…”
mentioning
confidence: 97%